2019
DOI: 10.1002/anie.201813716
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Synthesis of Functionalized Dihydropyridines, Pyridines, and 2H‐Pyrans: Heck Coupling of Monocyclopropanated Heterocycles

Abstract: Ap alladium-catalyzed coupling between aryl halides and monocyclopropanated pyrroles or furans has been developed, leading to valuable six-membered N-and Oheterocycles.A st he key step,as elective cleavage of the nonactivated endocyclic CÀCb ond of the 2-heterobicyclo-[3.1.0]hexane framework is achieved. The developed method offers access to highly functionalized piperidines,p yridines, and pyrans that are challenging to access by traditional methods.Supportinginformation and the ORCID identification number(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 79 publications
0
40
0
1
Order By: Relevance
“…Importantly, the use of water-tolerated Lewis acid, such as Yb(OTf) 3 , has markedly increased the yield of compound 34c up to 65%. Very recently, similar reaction conditions were applied on Boc-protected cycloadduct 7d by Reiser and co-workers, achieving bicyclic enecarbamates 35b containing an ester moiety at the C 5 position [43] (Scheme 18). They developed an innovative palladium-catalyzed synthesis of 1,2-dihydropyridines (37) starting from monocyclopropanated pyrroles (36), and after the NDA reaction, the obtained inverse cycloadducts 7d underwent a rearrangement reaction with Mo(CO) 6 The shortage of data on hetero-Cope rearrangement reactions of amide-NDA cycloadducts stimulated Pineschi and co-workers to investigate alternative reaction conditions to prepare dioxazine compounds, since they could be an interesting key intermediate for the synthesis of nitrogen-containing scaffolds [44].…”
Section: Elaboration Of Inverse Cycloadductsmentioning
confidence: 99%
“…Importantly, the use of water-tolerated Lewis acid, such as Yb(OTf) 3 , has markedly increased the yield of compound 34c up to 65%. Very recently, similar reaction conditions were applied on Boc-protected cycloadduct 7d by Reiser and co-workers, achieving bicyclic enecarbamates 35b containing an ester moiety at the C 5 position [43] (Scheme 18). They developed an innovative palladium-catalyzed synthesis of 1,2-dihydropyridines (37) starting from monocyclopropanated pyrroles (36), and after the NDA reaction, the obtained inverse cycloadducts 7d underwent a rearrangement reaction with Mo(CO) 6 The shortage of data on hetero-Cope rearrangement reactions of amide-NDA cycloadducts stimulated Pineschi and co-workers to investigate alternative reaction conditions to prepare dioxazine compounds, since they could be an interesting key intermediate for the synthesis of nitrogen-containing scaffolds [44].…”
Section: Elaboration Of Inverse Cycloadductsmentioning
confidence: 99%
“…reactions worked well with electron-donating (such as p-Me, m-OMe) and -withdrawing (such as halogens, À CN, À NO 2 ) groups except when highly electron-rich alkoxy substituents (such as OMe) were present at the para-position, which demonstrated that the electronic effect of this group had a certain influence on the reaction outcome. Cyclopropanated furans [11] and butenolides [12] find widespread applications as versatile synthetic intermediates for accessing a wide range of bioactive natural products and pharmaceutical agents. Considering that electron-rich olefins are known to undergo one-electron oxidation in polar solvents and in the presence of suitable oxidants, [8a-c] we speculated that dienones could also undergo such oxidation to generate radical cations.…”
Section: Introductionmentioning
confidence: 99%
“…We now report a successful implementation of the strategy to access cyclopropanated furans and butenolides from dienones under mild and metal-free reaction conditions. Cyclopropanated furans [11] and butenolides [12] find widespread applications as versatile synthetic intermediates for accessing a wide range of bioactive natural products and pharmaceutical agents.…”
Section: Introductionmentioning
confidence: 99%
“…Besides olefin metathesis, carbonyl–olefin metathesis is moving into the limelight, which shows exciting possibilities for the synthesis of heterocycles in general, and piperidines, in particular. Transition metal catalysis allows the transformation of unactivated carbon–carbon‐bonds in the presence of activated ones, which has been recently employed for the ring enlargement of cyclopropanated dihydropyrroles to piperidines . Likewise, catalytic C–H functionalization impressively demonstrates the possibility to achieve late stage functionalizations of heterocyclic moieties such as piperidines (Figure ) …”
mentioning
confidence: 99%
“…Transition metal catalysis allows the transformation of unactivated carbon-carbon-bonds in the presence of activated ones, which has been recently employed for the ring enlargement of cyclopropanated dihydropyrroles to piperidines. [20] Likewise, catalytic C-H functionalization impressively demonstrates the possibility to achieve late stage functionalizations of heterocyclic moieties such as piperidines (Figure 4). [21] Heterocyclic chemistry continues to thrive, bringing innovations to many areas of chemistry, biology and medicine.…”
mentioning
confidence: 99%